Analisis Isi Nilai Sosial Dan Budaya Film KKN Desa Penari - Arfian Suryasuciramadhan; Ayu Lestari; Keysha Nazwa Aulia; Priskania Widya Kusumawati; Siti Nur Ainnunisa Jahrah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Film, a performance in which there is meaning and a picture of life through the medium of moving images by utilizing technological sophistication that combines many elements in it. Movies are created from unrest or influence from real life to provide a message. KKN in Desa Penari is a movie that is based on the phenomenon of KKN that occurs in Indonesia. The story set in the countryside does create a horror narrative wrapped in many meanings contained in it both for students and the community itself. The purpose of this research is to find out the information and meaning contained in the KKN Film in Penari Village whose implementation is related to social and culture in society. The method used in this research is the Descriptive Qualitative research method.